State-of-the-art review on automated lumen and adventitial border delineation and its measurements in carotid ultrasound. (September 2018) - Kumar, P Krishna; Araki, Tadashi; Rajan, Jeny; Laird, John R; Nicolaides, Andrew; Suri, Jasjit S.; ,
Highlights: State-of-the-art methods and systems for the measurement of carotid lumen diameter (LD) and inter-adventitial diameter (IAD). Challenges and recent trends in carotid lumen segmentation and future perspectives. Clinical Significance and implications of carotid LD and IAD. A novel method for quantification of stenosis and patient risk assessment based on carotid LD. Abstract: Background and objective: Accurate, reliable, efficient, and precise measurements of the lumen geometry of the common carotid artery (CCA) are important for (a) managing the progression/regression of atherosclerotic build-up and (b) the risk of stroke. The image-based degree of stenosis in the carotid artery and the plaque burden can be predicted using the automated carotid lumen diameter (LD)/inter-adventitial diameter (IAD) measurements from B-mode ultrasound images. The objective of this review is to present the state-of-the-art methods and systems for the measurement of LD/IAD in CCA based on automated or semi-automated strategies. Further, the performance of these systems is compared based on various metrics for its measurements. Methods: The automated algorithms proposed for the segmentation of carotid lumen are broadly classified into two different categories as: region-based and boundary-based. These techniques are discussed in detail specifying their pros and cons. Further, we discuss the challenges encountered in the segmentation process along with its quantitative assessment. Lastly, we present stenosis quantification and risk stratification strategies. Results: Even though, we have found more boundary-based approaches compared to region-based approaches in the literature, however, the region-based strategy yield more satisfactory performance. Novel risk stratification strategies are presented. On a patient database containing 203 patients, 9 patients are identified as high risk patients, whereas 27 patients are identified as medium risk patients. Conclusions: We have presented different techniques for the lumen segmentation of the common carotid artery from B-mode ultrasound images and measurement of lumen diameter and inter-adventitial diameter. We believe that the issue regarding boundary-based techniques can be compensated by taking regional statistics embedded with boundary-based information.